Functionalised magnetic nanoparticles for uranium adsorption with ultra-high capacity and selectivity. Issue 7 (26th January 2018) - Calì, E.; Qi, J.; Preedy, O.; Chen, S.; Boldrin, D.; Branford, W. R.; Vandeperre, L.; Ryan, M. P.
Abstract : A uranium-selective and high-capacity magnetic nanosorbent particle with ultra-fast up-take kinetics devised for water decontamination. Abstract : The removal of radioactive contaminants from the environment for safe and efficient waste disposal is a critical challenge, requiring the development of novel selective and high-capacity sequestering materials. In this paper the design of superparamagnetic iron oxide nanoparticles (SPIONs) as highly efficient magnetic-sorbent structures for uranium (U(vi )) separation is described. The nanosorbent was developed by surface functionalisation of single crystalline magnetite (Fe3 O4 ) nanoparticles with a phosphate-based complex coating. This new design allowed for the development of a magnetically separable ultra-effective sorbent, with a measured U(vi ) sorption capacity of ∼2333 mg U per g Fe (1690 mg U per g Fe3 O4 NP), significantly higher than everything previously reported. Based on TEM analysis, it is proposed that these properties are the result of a multi-layer ligand structure, which enables a high degree of U-incorporation compared to conventional surface-ligand systems. Moreover, the phosphate-NP construct ((PO) x -Fe3 O4 ) shows exceptionally high specificity for the sequestration of U(vi ) in solution at pH 7. Adsorption tests in the presence of competing ions, such as Sr(ii ), Ca(ii ) and Mg(ii ), showed high selectivity of the nanoparticles for U(vi ) and extremely rapid kinetics of contaminant removal from solution, with the total amount of uranyl ions being removed after only 60 seconds of contact with the NPs. The results presented in this paper highlight the potential of such a phosphate-functionalised magnetic nanosorbent as a highly effective material for the remediation of U(vi ) from contaminated water and industrial scenarios.